A rapid and ultrasensitive colorimetric biosensor based on aptamer functionalized Au nanoparticles for detection of saxitoxin. Issue 26 (17th April 2020) - Qiang, Le; Zhang, Yu; Guo, Xin; Gao, Yakun; Han, Yingkuan; Sun, Jun; Han, Lin
Abstract : We demonstrate a facile and ultrasensitive colorimetric sensor based on gold nanoparticles (Au NPs) and aptamer (Au NPs-aptamer biosensor) for specific and quantitative detection of STX. Abstract : Saxitoxin (STX) is one of the most important marine toxins which affects the safety of domestic water. Rapid, sensitive and selective recognition of STX is crucial in environment monitoring. Here, we demonstrate a facile and ultrasensitive colorimetric sensor based on gold nanoparticles (Au NPs) and aptamer (Au NPs-aptamer biosensor) for specific and quantitative detection of STX. The aptamer reacts specifically with STX, resulting in the aggregation of Au NPs and the color change of the Au NP solution. The lowest detection concentration of the colorimetric sensor is 10 fM (3 fg mL −1 ), and a good linear relationship ( R 2 = 0.9852) between the absorbance ratio and STX concentrations (10 fM to 0.1 μM) indicates that our Au NPs-aptamer biosensor can be used for quantitative sensing of STX. The detection time of STX is 30 minutes, and the sensor is successfully applied in the specific detection of STX in seawater. The Au NP-aptamer biosensor shows great potential in practical applications to monitor environmental pollution, marine aquaculture pollution, and seafood safety.